Institute for Nuclear Problems: 30 years of research activity - Baryshevsky, Vladimir G.; Maksimenko, Sergey A. (Journal of the Belarusian State University. Physics, 2017)
The Institute for Nuclear Problems of Belarusian State University has been founded 30 years ago, in October, 1986. A short introduction into history and main fields of research activity of the Institute is given. A set of most important results achieved in the Institute during past years both in fundamental and applied research is presented.